Analysis of the Effect of Social Capital on Brand Performance with the Mediating Role of Employees’ Brand Citizenship Behavior - Naser Seifollahi (پژوهش‌های مدیریت عمومی)
AbstractOrganizational Social CapitalThe history of social capital goes back to classical economists like Adam Smith and John Stuart Mill and sociologists like Max Weber who used cultural factors to analyze economic phenomena. Social capital has been defined as the total of real and potential resources hidden inside, available and emerging from the network of relationships belonging to an individual or social unit (Joeng & et al, 2021). According to Putnam, social capital refers to the connections between people - social networks and mutual and reliable norms that arise from them. According to these definitions, social capital is defined as an asset that exists in social relationships between individuals, networks and communities to achieve mutual benefits (Tuominen, & Haanpää, 2022).Brand PerformanceBrand performance means the degree of brand success in the market and tends to measure the strategic success of a brand (Lee et al, 2008). The success of a business undoubtedly comes from the performance of that business's brand (De Chernatony et al, 2004). Brand performance is a measure of a brand's results against business and marketing goals. While brand delivery focuses on how branding is executed during the marketing campaign, brand performance measures campaign results to see how effective branding has been for the business. And since each brand is different, performance varies significantly from one brand to another (Wu et al, 2020).The factors that affect the company's performance have two main dimensions: objective (or financial) and judgmental (or non-financial). The methods of measuring financial parameters to evaluate the company's performance suffer from the limitation that the marketing department's efforts in creating long-term financial value have not been considered. Therefore, it is essential that academics consider more dimensions than financial numbers to create a comprehensive performance measure. Therefore, non-financial performance measures belonging to perceptual and behavioral categories such as brand, customer satisfaction and loyalty are considered, acknowledging that an integrated and strategic view of performance evaluation is required (Sarkar et al, 2021).Brand citizenship behaviorBrand citizenship behavior is an employee's brand altruistic behavior to increase brand equity. It enables employees to automatically display altruistic brand behavior such as good service behavior that can improve brand image. Although this concept refers to employee behaviors toward a brand, it can also be extended to customer behaviors, as customers are more likely to support a brand that exhibits altruistic behaviors. Brand citizenship behavior includes all behaviors that are performed by the organization's internal stakeholders and to empower the organization's brand personality. According to Zeppelin, brand citizenship behavior is defined as a task outside the job description, but in later researches, brand citizenship behavior was developed not only to behaviors outside the job description, but also to behaviors inside the job (Kirimi et al., 20) 16).Materials and Methods The current research method is correlation through structural equation modeling. The research was applied in terms of purpose and descriptive-survey in terms of method and correlation type. The statistical population of the research included all the employees of the companies producing dairy products in Ardabil province, according to Cochran's formula, 260 people were selected as a sample, and these people were selected from the statistical population as available. Three standard questionnaires of social capital (Nahapiet & Ghoshal, 1998), brand performance (Punjaisri & et al, 2009) and brand citizenship behavior (Marzban brand citizenship behavior questionnaire, 2016) were used to collect data. Structural equation modeling method was used to analyze the hypotheses. The data was analyzed using SPSS and AMOS software. Validity was checked and confirmed using confirmatory factor analysis and reliability by Cronbach's alpha.Discussion and Results Today, corporate social responsibility is a very important issue in management circles. Organizations and companies are becoming more interested in the discussion of social responsibility day by day and are paying more attention to this issue. Corporate social responsibility, through its effect on brand performance, can be an important factor in the growth and increase of the market share of companies producing dairy products, which is a long-term strategy and planning for increasing social capital and brand citizenship behavior, and as a result, strengthening performance. They have a company brand. Based on the image of their brand in the minds of customers, companies producing dairy products should strengthen the brand citizenship behavior of employees and improve the performance of their brand by strengthening the social capital of employees. Social capital is an important resource for individuals and can greatly affect their ability to act and the visible quality of their work life. The higher the social capital of a company, the better the performance of the brand and also the brand citizenship behavior of the employees in the company. Social capital by increasing the creation of proper relationship between employees and creating and strengthening common values in the company affects the branding activities of the organization and strengthens the behaviors in accordance with the brand promise towards the customers.ConclusionThe findings of this research confirm that social capital has a significant and positive effect on brand performance, and the brand citizenship behavior of employees also plays a mediating role between social capital and brand performance. In case of further expansion of social capital and brand citizenship behavior in companies producing dairy products, it can be expected that the performance of the brand will be strengthened and lead to the creation of a sustainable competitive advantage over competitors in the field of further expansion of social capital and brand citizenship behavior. They do not have a clear strategy.Therefore, in today's era, companies should pay special attention to the performance of their brand in addition to environmental dynamics, in addition to using their physical assets, and by strengthening the social capital of employees and brand citizenship behavior in the organization, they should cause the growth and development of their brand among competitors.